Lycopene in Combination with Insulin Triggers Antioxidant Defenses and Increases the Expression of Components That Detoxify Advanced Glycation Products in Kidneys of Diabetic Rats - Figueiredo, Ingrid Delbone [UNESP]; Lima, Tayra Ferreira Oliveira [UNESP]; Carlstrom, Paulo Fernando [UNESP]; Assis, Renata Pires [UNESP]; Brunetti, Iguatemy Lourenço [UNESP]; Baviera, Amanda Martins [UNESP] (MDPI, 2024)
BACKGROUND: Biochemical events provoked by oxidative stress and advanced glycation may be inhibited by combining natural bioactives with classic therapeutic agents, which arise as strategies to mitigate diabetic complications. The aim of this study was to investigate whether lycopene combined with a reduced insulin dose is able to control glycemia and to oppose glycoxidative stress in kidneys of diabetic rats. METHODS: Streptozotocin-induced diabetic rats were treated with 45 mg/kg lycopene + 1 U/day insulin for 30 days. The study assessed glycemia, insulin sensitivity, lipid profile and paraoxonase 1 (PON-1) activity in plasma. Superoxide dismutase (SOD) and catalase (CAT) activities and the protein levels of advanced glycation end-product receptor 1 (AGE-R1) and glyoxalase-1 (GLO-1) in the kidneys were also investigated. RESULTS: An effective glycemic control was achieved with lycopene plus insulin, which may be attributed to improvements in insulin sensitivity. The combined therapy decreased the dyslipidemia and increased the PON-1 activity. In the kidneys, lycopene plus insulin increased the activities of SOD and CAT and the levels of AGE-R1 and GLO-1, which may be contributing to the antialbuminuric effect. CONCLUSIONS: These findings demonstrate that lycopene may aggregate favorable effects to insulin against diabetic complications resulting from glycoxidative stress.
Keywords: antidiabetic activity; diabetic complications; glycoxidative stress; glyoxalase; natural bioactives; paraoxonase